Juara - STKIP Muhammadiyah Kuningan. Pendidikan Jasmani Kesehatan dan Rekreasi (Department of Physical Education, Health and Recreation, STKIP Muhammadiyah Kuningan, 2016)
Research results in the fields of Sports Education & Recreation, Sports Management, and Sports Science.
Keywords: Sports sciences : Indonesia : Periodicals; Sports sciences : Periodicals; Physical education and training : Study and teaching : Indonesia : Periodicals; Physical education and training : Study and teaching : Periodicals; Physical education and training : Study and teaching; Sports sciences; Indonesia